Long‐Term 15N Balance After Single‐Dose Input of 15N‐Labeled NH4+ and NO3− in a Subtropical Forest Under Reducing N Deposition. Issue 7 (27th July 2021) - Xie, Danni; Duan, Lei; Si, Gaoyue; Liu, Wenjing; Zhang, Ting; Mulder, Jan
Abstract: Nitrogen (N) deposition in Europe and North America decreased in the 1990s, whereas N deposition in China began to decline in the early 2010s. The response of temperate forests to decreasing N deposition implied a delay recovery, but it remains unknown whether recovery in subtropical forests follows a similar trend. Therefore, the effects of decreased N deposition on N leaching were simulated in an N‐saturated forest in southwest China following ten years of N application 4.00 g N m −2 yr −1 . The addition of N (NH4 + or NO3 − ) was stopped in 2014. In 2017, a single in‐situ 15 N addition as NH4 + or NO3 − was performed to trace the fate of N under reducing N deposition. Combining the monitoring results of the N fluxes and 15 N fates, both the actual N leaching and contribution of a "new" N input to N leaching were significantly reduced in response to decreasing the N input. The termination of N addition resulted in immediate decreases in the N mineralization and immobilization rates, which were even lower than those in the control plots with moderate (naturally occurring) deposition reduction. The ratio of N leaching from mineralization was also reduced, implying the critical role of N mineralization in the recovery from N saturation. Because the forest was still N‐saturated, decreasing N deposition slightly reduced the N leaching to the gross N input ratio (including both N deposition and N mineralization). The significant decrease in the ratio and thus leaching recovery may occur due to a significant N deposition reduction. Key Points: 15 N tracing experiments were carried out under both increasing and decreasing N deposition, to study the fate of NH4 + and NO3 − separately After N deposition decreased, N leaching to N deposition ratio increased inversely and N mineralization delayed leaching recovery N leaching to gross N input ratio decreased after N deposition declined in N‐saturated subtropical forest, in accord with temperate forest